Tantangan Implementasi Kurikulum Merdeka Pada Sekolah Dasar yang Berbasis Islami: Evaluasi dan Solusi - Aulyfannisah, Masayu Safira (Journal of Innovation in Teaching and Instructional Media, 2024)
The Merdeka Curriculum offers a variety of learning approaches that allow students and teachers to choose material that suits each learning need to achieve optimal learning. This research uses qualitative methods, the research location is at one of the Islamic schools in Palembang. This research involved eight sources as informants who were selected using purposive sampling techniques. The data in this research was collected through two data collection techniques, namely interviews and distributing questionnaires to participants. The results of the study stated the lack of school readiness in accepting and implementing the independence policy, especially English language teaching. The novelty of this study is that the successful implementation of the independence curriculum requires Independent Curriculum Training, English Language Training, Facilities and Media. This study contributes to the world of education, especially in the implementation of the Independent Curriculum based on Islamic values ​​in Elementary Schools.